2016
DOI: 10.1063/1.4940121
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a high repetition rate capillary discharge waveguide

Abstract: A hydrogen-filled capillary discharge waveguide operating at kHz repetition rates is presented for parameters relevant to laser plasma acceleration (LPA). The discharge current pulse was optimized for erosion mitigation with laser guiding experiments and MHD simulation. Heat flow simulations and measurements showed modest temperature rise at the capillary wall due to the average heat load at kHz repetition rates with water-cooled capillaries which is promising for applications of LPAs such as high average powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…Also, MHD simulations presented in Ref. [32] indicate that current nonuniformity is minimized at lower peak current and higher fill pressures. This could imply that operating a 440 A peak discharge pulse at 200 A timing (trailing edge) is more detrimental to the emittance than using a 200 A peak discharge pulse at peak timing.…”
Section: Experimental Observationmentioning
confidence: 93%
See 1 more Smart Citation
“…Also, MHD simulations presented in Ref. [32] indicate that current nonuniformity is minimized at lower peak current and higher fill pressures. This could imply that operating a 440 A peak discharge pulse at 200 A timing (trailing edge) is more detrimental to the emittance than using a 200 A peak discharge pulse at peak timing.…”
Section: Experimental Observationmentioning
confidence: 93%
“…Based on concepts revived from the 1950s ion accelerator community [24][25][26][27], recently Ref. [28] demonstrated that discharged plasma lenses [29][30][31][32] have the potential to be of great value to compact accelerator applications, due to tunability, high-field gradients (>3000 T=m), and radial focusing symmetry. For example, I 0 ¼ 600 A for a R ¼ 0.25 mm capillary yields a field gradient of 1800 T=m, corresponding to a focal length of 5 cm for a L ¼ 30 mm long structure and 1 GeV electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Investigation into the lifetime of plasma capillaries over millions of kHz-rate, high-voltage discharges has shown promising solutions that could be implemented at FLASHForward [45]. The heating of capillaries from millions of plasma ignitions and wall erosion from kHz repetition discharges have been studied.…”
Section: (C) Capillary Lifetime and Coolingmentioning
confidence: 99%
“…Active plasma lenses [21] (APLs) potentially offer an elegant solution with their compact size, azimuthally symmetric focusing, and high magnetic field gradients, which have been shown to exceed 3 kT/m [22]. Recent studies indicate that nonuniform current densities may form inside discharge capillary based APLs [23][24][25][26][27], leading to nonlinear magnetic field gradients and, subsequently, emittance deterioration [28,29].…”
Section: Introductionmentioning
confidence: 99%